(3TQM GdeaUds - (3jYjT Hf Ydj Hf jYjT GHf CHj GdSQGjG eMeO Hf Ydj, CHh GdHbGA, ehab GdOjf GdCSOj GdehUdj, GHf jYjT , GHf GdUGfY , J (B643 (3g`s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3aUd(B: (3bGd UGMH GdcJGH(B: (3hceG cGfJ GdUaI hab GdehUha aj EYQGHg s
(3BNQgG (B:s
(3hGdGSe gh HceGdg YfO GdHUQjjf, hbGd Gdchajhf GdESe(B: (3GdgGA hMOgG hGdhGh eRjOI, hGMJLhG HPdc Hbhd GdTGYQ s
(3fSNI KGfjIs
(3LRA efgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
Keywords: (3GdfMhs